Penerapan Model Project Based Learning Pada Pelajaran Produk Kreatif dan Kewirausahaan Sebagai Upaya Meningkatkan Minat Berwirausaha Peserta Didik - Hendras Setianingrum (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
The subject of creative products and entrepreneurship is one of the compulsory subjects taught in Vocational High Schools, has a strategic meaning in forming entrepreneurial attitudes and character, providing more knowledge and skills to students about the world of business and entrepreneurship which is expected to foster students' interest in entrepreneurship. In the midst of intense competition in the world of work, students are expected to be able to create their own business opportunities. Through the application of the project based learning learning model, it is hoped that it can increase students' interest in entrepreneurship,because in addition to getting theoretical learning in solving problems they will be exposed to the real world of business, producing skills in the form of projects ranging from learning to process, manage and grow their creative ideas to the fullest. . Based on research analysis using literature studies, it shows that the application of the Project Based Learning learning model can increase students' interest in learning entrepreneurship, especially in learning Creative Products and Entrepreneurship. , students are able to provide ideas for work in the form ofinnovative and creative products. In the implementation it is very effective and fun for students, because it is able to develop the abilities of students, while the teacher acts as a facilitator, according to the syntax in project-based learning where students are directed to make projects/products, starting from previously scheduled planning to reporting results to the teacher.